Single-molecule force spectroscopy on histone H4 tail-cross-linked chromatin reveals fiber folding - Kaczmarczyk, Artur (2018)
The eukaryotic genome is highly compacted into a protein-DNA complex called chromatin. The cell controls access of transcriptional regulators to chromosomal DNA via several mechanisms that act on chromatin-associated proteins and provide a rich spectrum of epigenetic regulation. Elucidating the mechanisms that fold chromatin fibers into higher-order structures is therefore key to understanding the epigenetic regulation of DNA accessibility. Here, using histone H4-V21C and histone H2A-E64C mutations, we employed single-molecule force spectroscopy to measure the unfolding of individual chromatin fibers that are reversibly cross-linked through the histone H4 tail. Fibers with covalently linked nucleosomes featured the same folding characteristics as fibers containing wild-type histones but exhibited increased stability against stretching forces. By stabilizing the secondary structure of chromatin, we confirmed a nucleosome repeat length (NRL)-dependent folding. Consistent with previous crystallographic and cryo-EM studies, the obtained force-extension curves on arrays with 167-bp NRLs best supported an underlying structure consisting of zig-zag, two-start fibers. For arrays with 197-bp NRLs, we previously inferred solenoidal folding, which was further corroborated by force-extension curves of the cross-linked fibers. The different unfolding pathways exhibited by these two types of arrays and reported here extend our understanding of chromatin structure and its potential roles in gene regulation. Importantly, these findings imply that chromatin compaction by nucleosome stacking protects nucleosomal DNA from external forces up to 4 piconewtons.